Reflective Participant Observation: Opportunities and Dilemmas - Witkowski, Maciej (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
The author presents the practical sense and key assumptions used in research projects based on participatory observation data. The article has an interdisciplinary and universal character – the discussed approach does not refer only to the specific needs of pedagogy, but is applicable to all sub-disciplines of modern social sciences, and in each case it should be adapted to the subject of research. Participatory observation is most often treated as a research technique, but in some approaches –especially in undertakings carried out in cultural anthropology – it can be the mainresearch method. In such an approach, a research technique is a clearly defined wayof creating, and then using in the emerging interpretation, field notes. Participatory observationis usually used in conjunction with the implementation of a series of individualor group in-depth interviews.